SYNTHESIS AND IN SILICO STUDY OF 4,4-DISUBSTITUTED (E)-2-[(4-SULFAMOYLPHENYL) HYDRAZINEYLIDENE]TETRAHYDROTHIOPHENE-1,1,3-TRIOXIDES - Kolomiets, A.Y.; Balabushko, M.O.; Milokhov, D.S.; Poliudov, A.O.; Volovenko, Y.M.; Dobrydnev, A.V. (Reports of the National Academy of Sciences of Ukraine, 2024)
An efficient method for the synthesis of 4,4-disubstituted (E)-2-[(4-sulfamoylphenyl)hydrazineylidene]tetrahydrothiophene- 1,1,3-trioxides, including those with spirocyclic substituents, has been developed. The method is based on the azo coupling of cyclic β-ketosulfones with 4-sulfamoylbenzene diazonium acetate ((obtained in situ from the corresponding 4-aminobenzenesulfonamide). Detailed analysis of NMR spectra and DFT calculations unambiguously established the structure of the studied compounds. This class of compounds is considered as a new generation of sulfa drugs with a wide spectrum of biological activity. In silico studies have shown that the studied compounds fulfill the requirements of drug affinity, have a promising ADMET profile and possess potential antibacterial and antitumor activity. In particular, molecular docking showed that the studied compounds have high affinity for binding to dihydropteroate synthetase (1AD1), which affects the growth of Staphylococcus aureus, and CLK4 protein (6FYV), one of the effects of which is the stimulation of malignant tumor formation.